2019
DOI: 10.1016/j.ejmp.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body habitus and image quality and radiation dose in chest X-ray examinations: A phantom study

Abstract: Ti t l e R el a tio n s hi p b e t w e e n b o dy h a bi t u s a n d i m a g e q u ality a n d r a di a tio n d o s e in c h e s t x-r a y e x a mi n a tio n s : a p h a n t o m s t u dy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This variation in exposure alterations has been attributed to the MRP's training on either film screen or digital radiography, past education as well as work practices. However, when a chest phantom was used by Al-Murshedi et al, [42] , AEC did not result in optimal image quality and resulted in reduced pathology detection in instances where the kVp was high. MRPs may therefore be required to manually set exposure factors which may be improved by maintaining records of exposure factors received by this patient pop-ulation [45] .…”
Section: General Radiographymentioning
confidence: 99%
See 1 more Smart Citation
“…This variation in exposure alterations has been attributed to the MRP's training on either film screen or digital radiography, past education as well as work practices. However, when a chest phantom was used by Al-Murshedi et al, [42] , AEC did not result in optimal image quality and resulted in reduced pathology detection in instances where the kVp was high. MRPs may therefore be required to manually set exposure factors which may be improved by maintaining records of exposure factors received by this patient pop-ulation [45] .…”
Section: General Radiographymentioning
confidence: 99%
“…In studies with phantoms, the distribution of adipose tissue at the anatomical area of interest was an important factor in determining the resultant image quality [42][43][44][45] . In their study with a pelvis phantom, Ismail et al, [44] reported a higher negative correlation (r = -0.83, p < 0.01) between the waist circumference and the image quality for abdominal images compared to that of the BMI and image quality (r = -0.73, p < 0.01).…”
Section: General Radiographymentioning
confidence: 99%
“…X‐ray technique selection in portable imaging can be a challenging hurdle in the ongoing effort to maintain image quality across a wide range of patient sizes 1–5 . Technologists have mostly been educated to operate digital detectors by targeting a single detector exposure level to reduce noise and avoid saturation 6–9 .…”
Section: Introductionmentioning
confidence: 99%
“…X-ray technique selection in portable imaging can be a challenging hurdle in the ongoing effort to maintain image quality across a wide range of patient sizes. [1][2][3][4][5] Technologists have mostly been educated to operate digital detectors by targeting a single detector exposure level to reduce noise and avoid saturation. [6][7][8][9] Digital detector image quality is primarily determined by quantum mottle, while global image contrast is maintained over a wide range of detector exposures.…”
Section: Introductionmentioning
confidence: 99%
“…However, physical characteristics such as the detective quantum efficiency [13,14] and image contrast [15,16] are still difficult to apply to clinical images, as the anatomical background has not been considered [1]. Moreover, analytical visual assessment methods, such as receiver operating characteristic curve analysis and visual grading characteristics analysis [17][18][19][20][21][22][23][24], are time-consuming and require advanced medical knowledge. Accordingly, they cannot be applied to large numbers of clinical images.…”
Section: Introductionmentioning
confidence: 99%